Questioni di tempo, narrativa e identità nei romanzi di Alessandro Baricco novecento e seta - Horváth, Kornélia (Verbum – Analecta Neolatina, 2008)
The aim of this paper is to provide an interpretation of Alessandro Baricco’s two novels, Novecento and Seta, from various perspectives. The problem of time, the forms of narration, the function of names and finally the problems of identity provide the main points of view of the analysis, which is partly based on some theoretical thoughts of Michail Bachtin and Paul Ricoeur.